2014
DOI: 10.1177/1043659614524794
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Awareness

Abstract: Implementation of learning to provide nurses language skills and cultural awareness of the diet, customs and beliefs of Iraqi people as well as the economic, political, and social factors that have an impact on their lives will promote quality nursing care and optimal health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Many studies have shown that communication and language barrier are among the most common problems in caring for foreign patients (Dotevall et al 2018; Luque et al 2018; Sevinç 2018). For example, it was reported in one study that problem occuring between Iraqi patients and US military nurses was due to communication and social and cultural variables (Goodman et al 2015). In another study, it was reported that a Swedish nursing student was often fearful of making mistakes when communicating in crosscultural care encounters (Jirwe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that communication and language barrier are among the most common problems in caring for foreign patients (Dotevall et al 2018; Luque et al 2018; Sevinç 2018). For example, it was reported in one study that problem occuring between Iraqi patients and US military nurses was due to communication and social and cultural variables (Goodman et al 2015). In another study, it was reported that a Swedish nursing student was often fearful of making mistakes when communicating in crosscultural care encounters (Jirwe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The data collection tool comprised student information and open‐ended question forms. The student information form covered questions regarding the sociodemographic characteristics of students, such as age, gender and class, whereas the open‐ended question form was developed by the authors on the basis of the literature (Douglas et al 2014; Goodman et al 2015; Tezel 2015; Table 1) and evaluated by two field experts in the development of questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Developed nations can improve healthcare for Muslims by observing the modesty and privacy requirements of Muslim women and paying special attention to the diet and gender restrictions of the patient (Goodman et al, 2015). In addition, providing space for prayers and serving permissible food also encourages Muslims to seek care (Tackett et al, 2018).…”
Section: Addressing Barriersmentioning
confidence: 99%
“…As nurses provide health services to individuals from different cultures (Douglas et al, 2011), they may encounter differences in ethnic origin, communication style and health‐related behaviours (Cicolini et al, 2015; Goodman et al, 2015). Nurses need to provide appropriate nursing care, taking into account the differences they face.…”
Section: Introductionmentioning
confidence: 99%